The Protective Effects of Lactobacillus plantarum KLDS 1.0344 on LPS-Induced Mastitis In Vitro and In Vivo - Chen, Qingxue; Wang, Song; Guo, Jiayao; Xie, Qinggang; Evivie, Smith Etareri; Song, Yue; Li, Bailiang; Huo, Guicheng (Frontiers in Immunology, 2021)
Cow mastitis, which significantly lowers milk quality, is mainly caused by pathogenic bacteria such as E. coli. Previous studies have suggested that lactic acid bacteria can have antagonistic effects on pathogenic bacteria that cause mastitis. We evaluated the in vitro and in vivo alleviative effects of L. plantarum KLDS 1.0344 in mastitis treatment in the current study. In vitro antibacterial experiments were performed using bovine mammary epithelial cell (bMEC) inflammation assays, followed by in vivo studies involving mastitis mouse models, respectively. In vitro results indicate that lactic acid was the primary substance inhibiting the E. coli pathogen. Meanwhile, pretreatment with Lactobacillus plantarum KLDS1.0344 can reduce cytokines' mRNA expression in the inflammatory response of bMEC induced by LPS. In vivo, the use of this strain reduced the secretion of inflammatory factors IL-6, IL-1β, and TNF-α, and decreased the activity of myeloperoxidase (MPO), and inhibited the secretion of p-p65 and p-IκBα, indicating that L. plantarum KLDS 1.0344 pretreatment can reduce the expression of inflammatory factors by inhibiting the activation of NF-κB signaling pathway, thus exerting prevent the occurrence of inflammation in vivo. Our findings show that L. plantarum KLDS 1.0344 has excellent properties as an alternative to antibiotics and can be developed into lactic acid bacteria preparation to prevent mastitis disease.